Women’s Empowerment to Increase Labor Force Participation in West Lampung Regency - Rudi Agus Hermawan (Jurnal Info Sains : Informatika dan Sains, 2025)
West Lampung Regency faces serious challenges in reducing the number of residents with seasonal unemployment status. This is due to the dependence of the community, the majority of whom work in the coffee farming sector, especially robusta coffee. This sector absorbs a lot of labor but has seasonal characteristics and is susceptible to market price fluctuations. The Open Unemployment Rate (TPT) in the district will increase in 2023. This is in line with the decline in the Labor Force Participation Rate (TPAK) which is due to the increase in the number of people taking care of the household, especially the female population. The writing of this paper uses a qualitative descriptive method by collecting data through holding focus group discussion (FGD) meetings, field visits, and literature studies to understand the causes of low TPAK and formulate effective policies. The selection of policy recommendations uses the Bardach method with 4 criteria. The purpose of writing this paper is to analyze and formulate policy recommendations that can increase the Labor Force Participation Level (TPAK) in West Lampung Regency, with a focus on empowering women, the majority of whom are hampered in household roles. The conclusion of this paper is to increase the Labor Force Participation Rate (TPAK) in West Lampung Regency, especially by overcoming the dominance of the female population who only take care of the household thereby reducing the female population's labor force participation, comprehensive regulations are needed. The chosen policy recommendation is to formulate and enact a Regional Regulation on Home Economic Empowerment